Image‐Derived Metrics Quantifying Hemodynamic Instability Predicted Growth of Unruptured Intracranial Aneurysms - Hong‐Ho Yang; James Sayre; Huy Dinh; Kambiz Nael; Geoffrey Colby; Anthony Wang; Pablo Villablanca; Noriko Salamon; Aichi Chien (Stroke: Vascular and Interventional Neurology, 2023)
Background Although image‐derived predictors of intracranial aneurysm (IA) rupture have been well explored, current understanding of IA growth is limited. Pulsatility index (PI) and wall shear stress PI (WSSPI) are important metrics measuring temporal hemodynamic instability. However, they have not been investigated in IA growth research. The present study seeks to verify reliable predictors of IA growth with comparative analyses of several important morphological and hemodynamic metrics between stable and growing cases among a group of unruptured IAs. Methods Using 3‐dimensional images, vascular models of 16 stable and 20 growing cases were constructed and verified using geodesic techniques. With an overall mean follow‐up period of 25 months, cases exhibiting a ≥10% increase in diameter were considered growing. Patient‐specific, pulsatile simulations were performed, and hemodynamic calculations were computed at 5 important regions of each aneurysm (inflow artery, aneurysm neck, body, dome, and outflow artery). Index values were compared between growing and stable IAs using ANCOVA controlling for aneurysm diameter. Stepwise multiple logistic regression and receiver operation characteristic analyses were conducted to investigate predictive models of IA growth. Results Compared with stable IAs, growing IAs exhibited significantly higher intrasaccular PI, intrasaccular WSSPI, intrasaccular spatial flow rate deviation, and intrasaccular spatial wall shear stress deviation. Stepwise logistic regression analysis revealed a significant predictive model involving PI at aneurysm body, WSSPI at inflow artery, and WSSPI at aneurysm body. Conclusions Our results showed that high degrees of hemodynamic variation within IAs are linked to growth, even after controlling for morphological parameters. Furthermore, evaluation of PI in conjunction with WSSPI yielded a highly accurate predictive model of IA growth. On validation in future cohorts, these metrics may aid in early identification of IA growth and understanding of IA remodeling mechanisms.